Ghrelin and its biochemical functions: Review - Aydin, Süleyman; Özkan, Yusuf; Caylak, Emrah; Aydin, Suna (Turkiye Klinikleri, 2006)
Ghrelin (also known as hunger hormone) is an orexigenic peptide hormone composed of 28 amino acid residues. It was discovered by Japanese scientists in 1999. After its discovery, it is considered a counterpart to leptin. Although this peptide is predominantly synthesized in the stomach, it is also expressed in the hypothalamus, pituitary gland, salivary gland, thyroid gland, intestine, kidney, heart, ?-cells of pancreatic islets, and gonads. Moreover, ghrelin mRNA is present in the following tissues; stomach, atrium, breast, buccal mucosa, esophagus, fallopian tube, fat tissue, gall bladder, human lymphocytes, ileum, kidney, left colon, liver, lung, lymph node, muscle, myocardium, ovary, pancreas, pituitary, placenta, prostate, right colon, skin, spleen, testis, thyroid, and venous vessels. Ghrelin plays an important role in the feeding behavior of animals and in appetite regulation in humans. Its secretion in the stomach depends on both acute and chronic changes in the energy balance. In the human organism, ghrelin stimulates secretion of growth hormone, prolactin, and ACTH. In addition to these main effects, ghrelin influences the cardiovascular and gastrointestinal systems. Plasma levels of ghrelin in humans correlate negatively with body mass index. Thus, its abnormal activity leads to over- or underweight. This review summarizes the current knowledge on ghrelin and its implications in health. Copyright © 2006 by Türkiye Klinikleri.
Ghrelin ve biyokimyasal fonksiyonlari
Keywords: Appetite regulation; Ghrelin